Extreme weather and residents’ pro-environmental behaviors - Wang, Yuwei; Wu, Yidong; Han, Zhijie (Frontiers in Environmental Science, 2022)
Raising residents' awareness of environmental protection and encouraging their pro-environmental behavior are essential components of promoting the development of green economic transformation. Based on the reality of frequent extreme weather worldwide, this paper establishes a regression model of extreme weather and residents' pro-environmental behaviors using CGSS2013 data and weather data. The results show that extreme weather has a significant inhibitory effect on residents' pro-environmental behaviors. Further analysis revealed that extreme weather reduced residents' environmental perceptions and knowledge, thus reducing their motivation to engage in pro-environmental behaviors.